(untitled) (Journal of Civil Engineering Researchers, 2022)
Since the parameters affecting the strengthening of cracked beams and their failure behavior after strengthening are very important, this research is devoted to the numerical investigation of the failure behavior of cracked concrete beams reinforced with steel sheet. The investigated beams have an initial crack in the middle of the span and are reinforced with a steel layer under the beam. Using the finite element method and non-linear static analysis, the bearing capacity of the samples, the growth and opening of the crack opening have been evaluated. First, in order to evaluate the accuracy of the modeling, the results obtained with the data obtained from the existing laboratory work were compared, and after ensuring the correctness of the modeling, the effect of changing various parameters, including sheet thickness, mechanical characteristics of concrete, initial crack length, was investigated. The results show that the load-opening diagrams of the crack openings have two maximum load points, the first and second maximum points increase with the increase of concrete strength and sheet thickness, and due to the increase in the initial crack length, the first maximum point decreases, while the maximum point The second remains almost unchanged.